Postpartum multiple vertebral fractures in a patient with osteogenesis imperfecta type I: A case report and literature review - Yumiko Miyazaki; Mizuki Hosokawa; Sho Kudo; Toshimichi Onuma; Makoto Orisaka; Yoshio Yoshida (Case Reports in Women's Health, 2024)
A 39-year-old woman with type I osteogenesis imperfecta reported experiencing back pain at 35 weeks of gestation. Two days following an elective cesarean section, the patient developed a Th12 vertebral compression fracture; 3 weeks postoperatively, she sustained an L3 vertebral compression fracture. The patient displayed a lumbar spine Z-score of −1.7; she subsequently discontinued breastfeeding, and treatment with active vitamin D was initiated. Genetic testing confirmed a diagnosis of osteogenesis imperfecta.